Building agricultural potential: Utilization of former land use rights by spatial planning - Harmoko, Hestu Adi; Wurarah, Rully Novie; Pattiasina, Thomas F. (Institute for Advanced Science Social, and Sustainable Future, 2024)
Background: Areas that were once Cultivation Rights (HGU) in Manokwari Selatan District are the subject of this research. Residents must follow the Regional Spatial Plan (RTRW) to use the land. This study aims to identify the potential for land development and analyze the current spatial allocation and arrangement in the former HGU area. Methods: Using system dynamic analysis, the study combined qualitative and quantitative approaches through observations and interviews. Result: The results show that once HGU areas could be developed into plantations or agriculture. This finding is based on land capability evaluated by considering ecological factors and local wisdom. Land use policies should be tailored to the potential and availability of land in this context. To increase the use of agricultural and plantation land, crop types suitable for soil capability can be selected based on land suitability. This research emphasizes the effect of policies on Kampung Gedi Merah's population growth. Using strategies to suppress the population growth rate is expected to reduce land conversion that is not by the RTRW spatial pattern. In 2023, 904 lived in this area without indicating land conversion. One of the critical challenges identified is the projected 33% decrease in land availability by 2030. Therefore, its land use needs to remain cording to RTRW directives. This research also provides recommendations to the local government to develop the potential of this land further so that interference with community use and control can be avoided.